Deception Toward British Muslims in Novel Home Fire (207) by Kamila Shamsie - Nesia Monika Al Nindita; Muhd. Al-Hafizh (English Language and Literature, 2019)
This thesis is an analysis of a novel written by Kamila Shamsie, entitled Home Fire (2017). It explored the issue about strategies carried out by the British Government and ISIS (Islamic States of Iraq and Syria) in an effort to deceive British Muslims and to what extent the implied author contributed to identify the issue. This novel analysis related to the concept of Orientalism and Islamophobia by Edward Said. The uses of the theory is based on the interpretation of the text and context of the novel. The result of this analysis showed deceptions have done by two groups with different strategies. First, deception by British Government by manipulation and limited rights. Meanwhile, ISIS create propaganda.